Efficacy and underlying mechanisms of berberine against lipid metabolic diseases: a review - Cai, Yajie; Yang, Qiaoning; Yu, Yanqiao; Yang, Furong; Bai, Ruina; Fan, Xiaodi (Frontiers in Pharmacology, 2023)
Lipid-lowering therapy is an important tool for the treatment of lipid metabolic diseases, which are increasing in prevalence. However, the failure of conventional lipid-lowering drugs to achieve the desired efficacy in some patients, and the side-effects of these drug regimens, highlight the urgent need for novel lipid-lowering drugs. The liver and intestine are important in the production and removal of endogenous and exogenous lipids, respectively, and have an important impact on circulating lipid levels. Elevated circulating lipids predisposes an individual to lipid deposition in the vascular wall, affecting vascular function. Berberine (BBR) modulates liver lipid production and clearance by regulating cellular targets such as cluster of differentiation 36 (CD36), acetyl-CoA carboxylase (ACC), microsomal triglyceride transfer protein (MTTP), scavenger receptor class B type 1 (SR-BI), low-density lipoprotein receptor (LDLR), and ATP-binding cassette transporter A1 (ABCA1). It influences intestinal lipid synthesis and metabolism by modulating gut microbiota composition and metabolism. Finally, BBR maintains vascular function by targeting proteins such as endothelial nitric oxide synthase (eNOS) and lectin-like oxidized low-density lipoprotein re-ceptor-1 (LOX-1). This paper elucidates and summarizes the pharmacological mechanisms of berberine in lipid metabolic diseases from a multi-organ (liver, intestine, and vascular system) and multi-target perspective.